Alexithymia reversion in psoriasis. (4th February 2019) - Sampogna, F.; Puig, L.; Spuls, P.; Girolomoni, G.; Radtke, M.A.; Kirby, B.; Brunori, M.; Bergmans, P.; Smirnov, P.; Rundle, J.; Castiglia, A.; Lavie, F.; et al.
Summary: Alexithymia means the inability to identify and express emotions. This condition is more common in people with chronic inflammatory diseases such as arthritis and inflammatory bowel disease. This international team previously showed, in the 'Epidemiological Study In Patients With Recently DiagnosEd PSOriasis' (EPIDEPSO), that alexithymia also affects adults with severe psoriasis; those affected are more likely to suffer from anxiety and depression and have a high risk of alcohol dependency and unemployment. An important question is whether alexithymia is a fixed personality trait, or a state which can improve if the psoriasis gets better: perhaps some psoriasis patients block their recognition of emotion as a defence against feeling stigmatised. To answer this, the authors followed up 467 of the original EPIDEPSO patients a year after starting systemic medication (i.e. it works on the whole body, rather than just being applied to the skin) or ultra‐violet light treatment. The prevalence of alexithymia reduced significantly from 26.7% to 18.8% and this improvement was most evident in patients younger than 40 years, who had suffered anxiety and depression, with psoriasis of recent onset, on visible areas, or that responded well to treatment. Patients who were clear or almost clear of psoriasis at follow‐up showed the greatest improvement in alexithymia. Hazardous alcohol use reduced by almost 3‐fold after 1 year. Although improvement in alexithymia was related to improvement in psoriasis, the authors acknowledge that the assessment tools they used are not perfect and that they have not established cause and effect. Nonetheless, they conclude that patients with alexithymia and severe psoriasis require psychological counselling as well as active psoriasis treatment. Abstract : Linked Article:  Sampogna et al. Br J Dermatol 2019;180 :397–403